Enhancing the Electrocatalytic Oxidation of 5-Hydroxymethylfurfural Through Cascade Structure Tuning for Highly Stable Biomass Upgrading - Jiang, Xiaoli; Ma, Xianhui; Yang, Yuanteng; Liu, Yang; Liu, Yanxia; Zhao, Lin; Wang, Penglei; Zhang, Yagang; Lin, Yue; Wei, Yen (Nano-Micro Letters, 2024)
Electrocatalytic 5-hydroxymethylfurfural oxidation reaction (HMFOR) provides a promising strategy to convert biomass derivative to high-value-added chemicals. Herein, a cascade strategy is proposed to construct Pd–NiCo2O4 electrocatalyst by Pd loading on Ni-doped Co3O4 and for highly active and stable synergistic HMF oxidation. An elevated current density of 800 mA cm–2 can be achieved at 1.5 V, and both Faradaic efficiency and yield of 2,5-furandicarboxylic acid remained close to 100% over 10 consecutive electrolysis. Experimental and theoretical results unveil that the introduction of Pd atoms can modulate the local electronic structure of Ni/Co, which not only balances the competitive adsorption of HMF and OH– species, but also promote the active Ni3+ species formation, inducing high indirect oxidation activity. We have also discovered that Ni incorporation facilitates the Co2+ pre-oxidation and electrophilic OH* generation to contribute direct oxidation process. This work provides a new approach to design advanced electrocatalyst for biomass upgrading. Highlights: 1 A novel cascade strategy is proposed to construct Pd-NiCo2O4 electrocatalyst. 2 First time discovery that Ni incorporation together with Pd loading is able to balance the competitive adsorption of OH– and 5-hydroxymethylfurfural. 3 Pd–NiCo2O4 promotes both the indirect and direct synergistic oxidation process. 4 Pd–NiCo2O4 catalyst exhibits extraordinary current density and excellent Faradaic Efficiency at a low potential.